STRUKTUR PENGUASAAN LAHAN DAN PENDAPATAN RUMAH TANGGA TANI (Studi Kasus di Kabupaten Kapuas dan Barito Selatan, Kalimantan Tengah) - SWASTIKA, DEWA K.S.; DJULIN, ADIMESRA; RAMLI, RACHMAT (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Agricultural sector in Central Kalimantan is expected to be a leading sector, especially to provide food and export. Therefore, improvement of technology is badly needed. The establishment of Assessment Institute for Agricultural Technology (AIAT) is aimed to do packaging and dissemination of mature and appropriate technology to meet the local stakeholders and beneficiaries needs. The appropriate technology should be based on the characteristics of local bio-physical and socio-economic environment. This article is aimed to present the baseline condition of land holding and income distribution of farmers in tidal swampy area of Kapuas and dry land in South Barito districts of Central Kalimantan. The results of the study showed that the average land holding in South Barito is larger than that of in Kapuas. Land holding is equally distributed among farmers, shown by Gini Index of 0.28 and 0.27, respectively, for ownership and operated. In Kapuas, land holding is relatively unequal, shown by gini index of 0.42 and 0.49, respectively, for ownership and operated. The annual household income in Kapuas was Rp 6.5 million or Rp 1,3 million/capita/year, with relatively unequal distribution among households, shown by Gini Index of 0.44. In South Barito, it was Rp 6.9 million or Rp 2,1 million/capita/year and has relatively equal distribution, reflected by Gini Index of 0.36. Most of household income is spent for food expenditure accounting for 67-69 percent in both districts. This performance indicating that the farmers still unable to improve their life quality, especially to meet their secondary needs. This implicitly shows that farmer’s capability to form capital accumulation for their farming is still very low. Therefore, the least cost new technology is required.
Keywords: Agricultural Sector, Leading Sector, Agricultural Technology, Land Holding, Income Distribution of Farmers, Appropriate Technology